ANALISIS PENGUKURAN PELAYANAN TERHADAP TINGKAT KEPUASAN PELANGGAN MEBEL DI PASAR MEBEL BIBIS SURAKARTA - TUTI EDIATI (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2016)
The purpose of this study was: (1) To determine the level of quality of services provided by the craftsmen in the furniture market Bibis Surakarta. (2) To determine the suitability of interest and customer expectations of the level of quality of services provided by the craftsmen in the furniture market Bibis Surakarta. This research was conducted in Surakarta Bibis Furniture market. The population in this study is all of the people in the city of Surakarta and surrounding areas. In this study were taken a sample of 100 customers with convinience sampling method. The results of this study can be concluded that in general the average level of the suitability of each dimension no one has reached 100 percent, so there are several dimensions that need to be improved, namely tangible dimension and the dimension of empathy. Dimensions closest customer expectations consist of dimensions of assurance, reliability and responsiveness,. While customer satisfaction index (CSI) to attribute the quality of services the furniture market Bibis Surakarta amounted to 84.979%. These results explain that the satisfaction level of overall service quality attributes assessed from customer the furniture market Bibis Surakarta has a level of Â